Boosted Ag/g-C3N4 prepared under microwave irradiation for photocatalytic activity of RhB under visible light - Azami, M. S. (2020)
The effluent of Rhodamine B (RhB) from industries causes a high impact toward contamination of the environment. Photocatalytic degradation has become a promising destructive technique to remove those dye from industrial. In this study, Silver/graphitic carbon nitride (Ag/g-C3N4) prepared using simplistic preparation using microwave irradiation in its place of normal calcination under furnace as heating media. The prepared photocatalyst was characterized by using Fourier transform infrared (FTIR), N2 adsorption-desorption, ultraviolet-visible diffuse reflectance spectra (UV-VIS/DRS). The deposited of Ag on g-C3N4 surface photocatalyst enhanced capability to extend the adsorption of visible light region. The texture of g-C3N4 affected after deposited with Ag and the bandgap energy of Ag/g-C3N4 narrowed from 2.7 eV to 2.31 eV significantly boosting and improved the efficiency of degradation RhB under visible light irradiation. The additional Ag on g-C3N4 revealed highest performance (98%) using RhB solution after exposed under visible light for 180 min. As a result, this works can give benefit to purify the effluent of toxic dyes as wastewater treatment.